2014
DOI: 10.3126/ijasbt.v2i2.10191
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of Different Mastitis Markers for Diagnosis of Sub-Clinical Mastitis in Cows

Abstract: Seven hundred ninety six milk samples from 266 quarters of 69 lactating cows were subjected to microbiological investigations for identification of pathogens. One hundred ninety bacterial isolates were recovered from 89 infected quarters, among these monomicrobial infection was found in 50 (56.2%) quarters, whereas, mixed infection was observed in 39 (43.8%) quarters. Bacterial isolates identified were Staph. chromogenes (49.47%), Staph. hyicus (21.1%), Staph. epidermidis (11.05%), Str. agalactiae (5.8%), Stap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 7 publications
1
17
2
Order By: Relevance
“…These results correspond with the findings of Galfi et al (2015). Chahar (2007) andLanger et al (2014) have reported lower percentage of true positive cases detected by Draminski mastitis test (38% and 7.6% respectively). Langer et al (2014) indicated that detection of subclinical mastitis with hand-held electrical conductivity meter was very low.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…These results correspond with the findings of Galfi et al (2015). Chahar (2007) andLanger et al (2014) have reported lower percentage of true positive cases detected by Draminski mastitis test (38% and 7.6% respectively). Langer et al (2014) indicated that detection of subclinical mastitis with hand-held electrical conductivity meter was very low.…”
Section: Resultssupporting
confidence: 91%
“…Chahar (2007) andLanger et al (2014) have reported lower percentage of true positive cases detected by Draminski mastitis test (38% and 7.6% respectively). Langer et al (2014) indicated that detection of subclinical mastitis with hand-held electrical conductivity meter was very low. Henningsson et al (2005) indicated that milk electrical conductivity is determined by type and concentration of ions, interactive influence of the ions and components contributing to milk viscosity (protein, fat, lactose).…”
Section: Resultsmentioning
confidence: 96%
“…However, our current findings are in disagreement with the findings of Tuteja et al (2013) who reported that a threshold of 6.4 or more is indicative of sub-clinical mastitis in dairy camels. Sensitivity of pH test observed in present study was higher than that reported by Langer et al (2014) for cows. Although, the specificity of this test was much lower than that reported by those authors, the low specificity observed for pH test suggests that pH of milk is not suitable method L.…”
Section: Discussioncontrasting
confidence: 55%
“…Again, Langer et al . [ 18 ] and Shitandi et al . [ 19 ] also reported average SCC values of 3-9 lakh cells/ml of milk in their study of bovine subclinical mastitis from Bikaner and Kenya.…”
Section: Discussionmentioning
confidence: 99%